KEBERFUNGSIAN KELUARGA DENGAN STRES PENGASUHAN IBU YANG MEMILIKI ANAK AUTISTIC SPECTRUM DISORDER (ASD) - Munawaroh, Latifatul; Amalia, Sofa (Universitas Muhammadiyah Jember, 2019)
Autistic spectrum disorder condition is what causes the mother to have parenting stress, so the mother can?t do parenting effectively and optimally. For that, the mother needed family functioning. For the end, the mother need family functioning to suppress the parenting stress. The aim of the study was to investigate the relationship of the family functioning in mother of children with autistic spectrum disorders (ASD). This study uses a correlation research design with a sampling technique that is incidental sampling, with the subjects of the 67. The instrument in this study uses the scale of The McMaster Family Assessment Device (FAD) and Parenting Stress Index (PSI). Pearson?s r correlation analysis was used to check correlations between assessments of family functioning and parenting stress to investigate correlations between results in mother. The outcome showed that there was an relationship of family functioning in mother of children with autistic spectrum disorder. The coefficient correlation (r) is -0,500 with a value of p = 0,000 <0.05. This shows that parents of children with ASD reported higher functioning of the family as a whole; they exhibited lower levels of parenting stress.